Ascorbate enhances iron uptake into intestinal cells through formation of a FeCl3-ascorbate complex - Thumser, Alfred E.; Rashed, Aswir Abd; Sharp, Paul A.; Lodge, John K. (Elsevier Science B.V., Amsterdam., 2010)
It has been well documented that ascorbate enhances iron uptake, with a proposed mechanism based on reduction to the more absorbable ferrous form. We have performed a study on the effects of ascorbate on ferric iron uptake in the human epithelial Caco-2 cell-line. Ascorbate increased uptake in a concentration- dependent manner with a significant difference between iron uptake and reduction. Uptake kinetics are characteristic of a non-essential activator and the formation of an Fe3+-ascorbate complex. This investigation provides evidence that ascorbate enhances the apical uptake of ferric iron into Caco-2 cells through the formation of a Fe3+-ascorbate complex. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Enterocyte iron uptake Ascorbate Ferric iron caco-2 cells nonheme iron colorimetric assay epithelial-cells expression transport absorption dmt1 bioavailability humans